Bio-concentration of Copper in the Oreochromis mossambicus and Safe Level of Consumption (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
Copper (Cu) is a heavy metal that is absorbed by organisms, such as Oreochromis mossambicus fish. This research aims to measure the bio-concentration of Cu in Oreochromis mossambicus and to predict the daily consumption of the fish. Samples of Oreochromis mossambicus fish were obtained from fishermen and collectors. The Cu concentration in the water and 30 fish was identified using the Atomic Absorption Spectrophotometry method. Questionnaires were employed to identify the demographic data of 101 respondents. The average concentration of Cu in the Oreochromis mossambicus fish and Rawapening Lake's water was 0.063 mg/l and 0.6 mg/kg, respectively. Furthermore, the bio-concentration of Cu in the Oreochromis mossambicus fish was 10.26Â±5.17 and categorized as low, while the average daily consumption of fish was 225Â±36.89 g/day. Therefore, it was concluded that the average bio-concentration and the daily consumption of the fish are in the low and safe category respectively.